Fluxo informacional em canais de atendimento ao cliente: estudo de caso nos Correios da Paraíba - Fernandes, Tatiana Falcão de Souza (2013)
This research analyzes the informational flow of the Customer Service Channels - CSC (Canais de Atendimento ao Cliente - CAC) of the Brazilian Post and Telegraph Company (Empresa de Correios e Telégrafos), Regional Board of Directors of Paraíba ECT/DR-PB by means of the perspective of information management (IM), questioning how the information of this flow influence the formulation of tactic actions for decision-making. The study aims at analyzing the informational flow of the CSCs of the Brazilian Post and Telegraph Company in its Regional Board of Directors of Paraíba. It is understood that the informational flow of the CSCs, if treated in a systematized way, is presented as valuable tool for the qualitative diagnosis of the offered services, besides attaining the legal requirements and fulfilling an evaluation in the processes of the provided products. Planning future actions and implementing corrective ones are the reasons that justify the study. With reference to the objectives, the methodology is classified as descriptive with quanti-qualitative approach of the case study type. In regard to data collection instruments, the study uses the guided interview and the documental analysis, categorizing data according to content analysis for interpreting them afterwards. As result of the study, it was observed that its aim is accomplished and by the indicators showed, the process seems to be effective. It is disseminated and understood by managers and operators as relationship instrument with the market and clients as well as the management. In spite of this, the potential of the data generated by the system, as its positive residual effect, does not produce direct effects or managerial actions for the continuous improvement of the organization and its final processes, especially the ones in medium and long term, either resulting from limiting factors of the process architecture and their control indicator, or due to limiting factors inherent to managers. From this viewpoint results the loss of competitiveness and the use of other costly and less efficient information sources, remaining the essential function of each manager, the one related to decision-making, submitted to results not always favorable to the company. In this context, We conclude that the management of CSC data flow provides information relative to diagnosis of the offered services, besides indicating the Regional Board of Directors positioning with regard to the company as a whole. It can be used for formulating tactic actions for decision-making and for continuous evaluation of management and organizational performance.